(untitled) (Scientific journal of the Fergana State University, 2023)
In this article we will talk about the changes that took place in the life of the Uzbek people during the Second World War, the situation behind the frontline of people’s lives, the courage and victory of women and their contribution to this process, the Uzbek girls who showed heroism in the battlefields, as well as the attention shown by the Government of Uzbekistan to the war veterans.